Bioinspired Synthesis of Illicium-Derived Neolignans and their Neurological Activity - Arnold, Robert (2021)
Illicium-derived neolignans present a wealth of structurally diverse species that arise initially from the oxidative phenolic coupling of common unit chavicol whereby it is proposed that intermediates can also undergo oxa-1,4-additions, oxidations, and dehydrating transformations. More recently, Illicium-derived neolignans have been tested for their neurological benefits in the promotion of growth and protection of developing neurons. This thesis presents a bioinspired approach for the total synthesis of simonsol C, simonsol F (previously unnamed) and simonsol G (previously unnamed), as well as their respective biomimetic transformations to simonsinol, macranthol and honokiol via plausible hydroxydienone intermediates. From simonsol F, the total synthesis of fargenin, simonsol E, simonsin A and two further possibly over-looked natural products epi-simonsol E and epi-simonsin A are described. Studies towards the synthesis of two possible diastereoisomers of fargenone A, “bowl” and “ladder” are presented. Efforts have begun towards an enantioselective synthesis of simonsol F. Illicium-derived neolignans, intermediates from synthesis and purposefully modified derivatives have been tested in an SAR study on the promotion of axon growth of primary cultured mouse cortical neurons.